RyR1-mediated Ca(2+) Leak and Ca(2+) Entry Determine Resting Intracellular Ca(2+) in Skeletal Myotubes - Eltit, José M. (American Society for Biochemistry and Molecular Biology, 2010)
The control of resting free Ca(2+) in skeletal muscle is thought to be a balance of channels, pumps, and exchangers in both the sarcolemma and sarcoplasmic reticulum. We explored these mechanisms using pharmacologic and molecular perturbations of genetically engineered (dyspedic) muscle cells that constitutively lack expression of the skeletal muscle sarcoplasmic reticulum Ca(2+) release channels, RyR1 and RyR3. We demonstrate here that expression of RyR1 is responsible for more than half of total resting Ca(2+) concentration ([Ca(2+)](rest)) measured in wild type cells. The elevated [Ca(2+)](rest) in RyR1-expressing cells is not a result of active gating of the RyR1 channel but instead is accounted for by the RyR1 ryanodine-insensitive Ca(2+) leak conformation. In addition, we demonstrate that basal sarcolemmal Ca(2+) influx is also governed by RyR1 expression and contributes in the regulation of [Ca(2+)](rest) in skeletal myotubes.